Sweet and cool dangers of vape - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (CodeBlue, 2023)
Our study on 28 vape liquids sold in Malaysia found 16 were labelled as containing sweeteners; only one openly declared the presence of a cooling agent. The sweeteners and synthetic cooling agents found in vape liquids may pose significant health risks.